Historical factors that have shaped the evolution of tropical reef fishes: a review of phylogenies, biogeography, and remaining questions - Cowman, Peter F. (Frontiers in Genetics, 2014)
Biodiversity patterns across the marine tropics have intrigued evolutionary biologists and ecologists alike. Tropical coral reefs host 1/3 of all marine species of fish on 0.1% of the ocean’s surface. Yet our understanding of how mechanistic processes have underpinned the generation of diversity is limited. However, it has become clear that the biogeographic history of the marine tropics has played an important role in shaping the diversity of tropical reef fishes we see today. In the last decade, molecular phylogenies and age estimation techniques have provided a temporal framework in which the ancestral biogeographic origins of reef fish lineages have been inferred, but few have included fully sampled phylogenies or made inferences at a global scale. We are currently at a point where new sequencing technologies are accelerating the reconstruction and the resolution of the Fish Tree of Life. How will a complete phylogeny of fishes benefit the study of biodiversity in the tropics? Here, I review the literature concerning the evolutionary history of reef-associated fishes from a biogeographic perspective. I summarize the major biogeographic and climatic events over the last 65 million years that have regionalized the tropical marine belt and what effect they have had on the molecular record of fishes and global biodiversity patterns. By examining recent phylogenetic trees of major reef associated groups, I identify gaps to be filled in order to obtain a clearer picture of the origins of coral reef fish assemblages. Finally, I discuss questions that remain to be answered and new approaches to uncover the mechanistic processes that underpin the evolution of biodiversity on coral reefs.